Viabilidade do cultivo da cana-de-açúcar irrigada para a produção de etanol - Nogueira, Helena Maria Camilo de Moraes (2016)
The production potential of the sugar-alcohol market and increased demand for ethanol makes the sugarcane the most important source of energy biomass for Brazilian agribusiness. This study aimed to evaluate the technical and economic performance of the culture of sugarcane under different levels of supplemental irrigation management for the production of ethanol in the Central Region of RS. The test was developed in the experimental area at the Polytechnic School of the Federal University of Santa Maria-RS in agricultural crops in the years 2013-2014 and 2014-2015. The treatments consisted of four blades of supplemental irrigation: 30, 60, 90 and 120% with control without irrigation. The variety used was RB93-5581 early cycle, planted on November 14, 2013. The experimental design was a randomized block design with six replications. Each experimental unit consisted of 4 rows with a spacing of 1 m and 5 m in length, each block of 20 m2 and a total area of 600 m2. Irrigation management was based on crop evapotranspiration, according to the methodology proposed by FAO. The irrigation system used was located drip between spacing each emitter and 0.2 m flow of 0.8 L h-1, and the frequency of irrigation was every seven days. It was carried out chemical analysis and physical soil. The monitoring of soil moisture was the time domain reflectometry (TDR). The following parameters were evaluated: tillering, plant height, diameter, leaf area, total weight, dry weight, yield, technological parameters, was also carried out the economic viability. The highest yield was in ratoon cane, with 190 t ha-1 in treatment 60% of ETc and the lowest yield was in the plant cane in the treatment of to rainfed 158.80 t ha-1. The difference between the highest and the lowest yield was approximately 11% and 7% in plant cane and tamp respectively. The rate of technical efficiency was maximum yield in 78% of ETc. The total mass and obtain dry mass increment of 20% to 25% by ratoon cane, respectively. The largest number of tillers, leaf area and the number of green leaves was in the treatment 120% of ETc. The deficit and excess moisture affected the number of tillers, plant height, the stalk diameter, leaf area, total mass, dry matter, yield and technological parameters for the production of ethanol. In sugarcane plant in rainfed and irrigated, the variable cost represented 54.40% and 66.81% and the fixed cost of 45.60% and 33.19%, respectively. The difference in the cost of production in rainfed and irrigated was 27.23% and 57.20% for the plant cane and tamp respectively. Presented economic viability, sugarcane grown in rainfed and 60% of ETc, with differences in the cost of production and net profit of 53.94% and 52.20%, with financial return in the year of implementation and 4 years and 4 months, respectively.